Antecedent Factors Affecting Organization Loyalty of Bank for Agriculture and Agricultural Cooperatives Employees - Meethom, Voraphong; Trisakhon, Chitralada (Journal of Liberal Arts RMUTT, 2025)
This study aims to examine the antecedents that affect employee organizational loyalty at the Bank for Agriculture and Agricultural Cooperatives (BAAC). The sample used in this research consists of 400 employees of BAAC, selected through stratified random sampling based on the proportion of employees at the head office and regional branches. Data were collected using a questionnaire and analyzed using frequency, percentage, mean, standard deviation, and hypothesis testing through partial least squares structural equation modeling (PLS-SEM). The research findings revealed that the majority of respondents were female, aged between 31-40 years, had a bachelor's degree, were married, and earned an average monthly income of 20,001 – 30,000 baht. Overall, they rated the antecedents and organizational loyalty at the highest level. The hypothesis testing showed that career advancement opportunities, leadership, and organizational commitment significantly affected employees' organizational loyalty at BAAC, with a statistical significance level of .05. The model demonstrated a prediction power of 92.7%. The research findings can be utilized to establish human resource management guidelines for enhancing employee loyalty. The bank should develop comprehensive welfare and benefits that meet employee needs, establish clear career paths, organize continuous skill development training programs, and promote leadership styles that encourage employee participation. These measures will help reduce turnover rates and increase the organization's operational efficiency in the long term.